Ayat-ayat Korupsi dalam Kitab Tafsir Fii Zhilalil Qur’an - Mustawa, Fahmi Khairi (Darul Yasin Al Sys, 2024)
This research discusses how Sayyid Qutb interprets verses related to corruption in Tafsir Fii Zhilalil Qur'an. The verses discussed in this research are based on corruption terms found in the Koran such as Ghulul, Risywah, Gasab, Khiyanah, Sariqah, Hirabah and Fasad. In order to be more focused in this research, the researcher limits this discussion to the terms corruption, namely: Risywah, Sariqah, Khianah. This type of research is qualitative research. Through this method, the author uses an approach to interpreting the Al-Qur'an from a thematic interpretation perspective. Namely collecting verses from the Qur'an that have the same purpose, arranging them chronologically as far as possible by explaining them, linking them to the surah where they are located, concluding and arranging these conclusions into a discussion framework so that they are visible from all aspects, and assessing them using criteria valid knowledge. The purpose of this research is to find out how Sayyid Qutb interprets Fii Zhilalil Qur'an in his interpretation of verses related to corruption. The results of this research, Risywah, in this case, is related to bribery in the judiciary, Sariqah, in this case, is related to the characterization of other people's assets in general, and Khianah, in this case, focuses on government officials who betray the trust that has been given to them. In interpreting the verses relating to corruption, Sayyid Qutb referred a lot to the interpretation of Ibn Kasir and Sayyid Qutb also took the opinions of the imams of the school of thought, namely: Imam Malik, Imam Syafi'i and Imam Ahmad did not reject the imposition of had law on the perpetrators. who steals other people's property.